Risking forgiveness after Charleston. (September 2019) - Shepherd, Aaron Pratt
Confronted by the White supremacists who had murdered their loved ones in June 2015, many of the family members of those killed at Mother Immanuel AME Church spoke words of forgiveness. The families' actions sparked sharp responses. In this essay, I will argue that critical responses misunderstood the practice of Black Christian forgiveness. I claim that Black Christian forgiveness is a practical political response to White supremacist violence, one richly grounded in the principles of personalism, the logic of nonviolence and a unique understanding of the meaning of the Christian gospel as a way to 'redeem the soul of America'.